Beyond the frame, beyond critique: Reframing place through more‐than visual participant‐photography. Issue 2 (5th March 2020) - Kelly, David
Abstract : There is an abundance of critique in tourism studies, human geography, and the social sciences that takes tourism‐driven depictions of place as its object. Indeed, the problematics of touristic imaginaries tend to fix, obscure, and exclude object‐subjects that more‐or‐less sit familiarly within/out frames of representation. Beyond the frame, beyond critique, there are practices that are less observed – practices that radically challenge the potency of ubiquitous "good life" narratives. This paper draws on visual ethnographic research methods in a frequently photographed but narrowly experienced place. Broome, in the remote Kimberley region of Australia, is an idyllic small urban town with a large tourism economy and operates as a service hub for extractive resource industries inland and offshore. Through the use of picture postcards and participant‐driven photography, this paper presents a narrative of "the beach" that demonstrates the fragility of normative "good life" tropes. By amplifying practices of inhabiting the beach that exceed representational critique and stimulate other ways of authoring place, this paper looks for an activism that resists settling on colonial ways of knowing place. Abstract : Colonial imaginaries fix, obscure, and exclude practices of Indigeneity that disrupt settler‐normativity. Beyond the colonial frame, this paper amplifies practices of inhabiting the beach that exceed representational critique and stimulate other ways of authoring place. This paper looks for an activism that resists settling on colonial ways of knowing place.